Field experience report - Cull, Brokke (My University, 2014)
Conclusion The education and experience that I gained through the public health program at Kansas State University has absolutely changed the way that I view the world. It has instilled in me a passion to continue research and work to improve the lives of those who need it most. Although I felt that I understood the context of public health when I began the program two years ago, I now reflect back and realize that many of the things that I believed to be true were, in fact, very far from it. I feel that this program has given me the tools to be a better researcher, public health professional and educated citizen. I am incredibly grateful for those who mentored me, worked with me, and encouraged me along the way. While this may be the closing of one chapter in my public health experience, I am confident that I have just begun to help advance the goals and mission of our profession.
Keywords: Walk Kansas; Gardening and Nutrition; Community programs; Public Health (0573)